Evaluation of Performance of Detection of Immunoglobulin G and Immunoglobulin M Antibody Against Spike Protein of SARS-CoV-2 by a Rapid Kit in a Real-Life Hospital Setting - Irungbam, Monica; Chitkara, Anubhuti; Singh, Vijay Kumar; Sonkar, Subash Chandra; Dubey, Abhisek; Bansal, Aastha; Shrivastava, Ritika; Goswami, Binita; Manchanda, Vikas; Saxena, Sonal; Saxena, Ritu; Garg, Sandeep; et al. (Frontiers in Microbiology, 2022)
Background: Antibody testing is often used for serosurveillance of COVID-19. ELISA and Chemiluminesence based antibody tests are quite sensitive and specific for such serological testing. Rapid antibody tests against different antigens are developed and effectively used for this purpose. But their diagnostic efficiency, especially in real-life hospital setting needs to be evaluated. So, the present study was conducted in a dedicated COVID-19 hospital in Delhi, India to evaluate the diagnostic efficacy of a Rapid antibody kit against receptor binding domain of spike protein of SARS-CoV-2. Material and Method: Sixty COVID-19 confirmed cases by RT-PCR were recruited and categorized as early, intermediate and late cases based on the days passed after their first RT-PCR +ve test report, 20 subjects in each category. Twenty samples from pre-covid era and twenty RT-PCR negative collected during the study period were taken as controls. IgM and IgG antibodies against RBD of spike (S) protein of SARS-CoV2 virus were detected by Rapid antibody test and compared with total antibody against the nucleocapsid (N) antigen of SARS-CoV-2 by Electrochemiluminescence based Immunoassay (ECLIA). Results: The detection of IgM against Receptor binding domain (RBD) of spike protein by rapid kit was less sensitive and less specific for the diagnosis of SARS-CoV-2 infection. However, diagnostic efficacy of IgG by rapid kit was highly sensitive and specific when compared with total antibody against N antigen measured by electrochemiluminiscence based immunoassay. Conclusion: It can be concluded that detection of IgM against RBD of S protein by rapid kit is less effective but IgG detection can be used as an effective diagnostic tool for SARS-COV-2 infection in real-life hospital setting.